Central pulmonary embolism in patients with Covid-19. Issue 7 (3rd July 2021) - Nordberg, Martin; Bankler, Sara; Everhov, Åsa H.; Saraste, Deborah
Abstract: Background: The purpose was to evaluate central pulmonary embolism (PE) in patients with Covid-19. The association with severe radiological pulmonary changes, prophylactic anticoagulation and ICU care was assessed. Methods: From 1 March until 31 May 2020, all in-hospital patients with a positive PCR for SARS-CoV-2-RNA and PE diagnosed with computed tomography pulmonary angiography were identified through diagnostic codes in medical charts. PE was characterised as central/peripheral and unilateral/bilateral. Covid-19 related lung changes were evaluated scoring the proportion of affected lung (max-score score 25) for all five lobes in both lungs. ICU and non-ICU patients were included and anticoagulant regimens were assessed. Results: Of 1162 patients with Covid-19, 41 were diagnosed with PE (cumulative incidence 3.5%), and of these 63.4% (=overall 2.2%) had central PE. PE on admission was present in 46.3%. No differences were seen in the distribution of central vs. peripheral PE in relation to prophylactic anticoagulation ( p=.317) . Of ICU patients 82.4% were diagnosed with central PE compared to 50.0% among non-ICU patients (p=.05). No association was observed between the presence of central PE and the extent of radiological Covid-19 changes (p=.451). Mild (0–12 p) and severe (13–25 p) pulmonary changes were seen in 63.4% and 36.6% of patients respectively. Conclusions: Overall, and especially in ICU-patients, a high proportion of central PE was seen and many were diagnosed at admission. No association between central PE and prophylactic anticoagulation, or the extent of pulmonary Covid-19 changes was observed.